Epstein-Barr Virus Exploits BSAP/Pax5 To Achieve the B-Cell Specificity of Its Growth-Transforming Program - Tierney, Rosemary (American Society for Microbiology, 2007)
Epstein-Barr virus (EBV) can infect various cell types but limits its classical growth-transforming function to B lymphocytes, the cells in which it persists in vivo. Transformation initiates with the activation of Wp, a promoter present as tandemly repeated copies in the viral genome. Assays with short Wp reporter constructs have identified two promoter-activating regions, one of which (UAS2) appears to be lineage independent, while the other (UAS1) was B-cell specific and contained two putative binding sites for the B-cell-specific activator protein BSAP/Pax5. To address the physiologic relevance of these findings, we first used chromosome immunoprecipitation assays and found that BSAP is indeed bound to Wp sequences on the EBV genome in transformed cells. Thereafter, we constructed recombinant EBVs carrying two Wp copies, both wild type, with UAS1 or UAS2 deleted, or mutated in the BSAP binding sites. All the viruses delivered their genomes to the B-cell nucleus equally well. However, the BSAP binding mutant (and the virus with UAS1 deleted) showed no detectable activity in B cells, whether measured by early Wp transcription, expression of EBV latent proteins, or outgrowth of transformed cells. This was a B-cell-specific defect since, on entry into epithelial cells, an environment where Wp is not the latent promoter of choice, all the Wp mutant viruses initiated infection as efficiently as wild-type virus. We infer that EBV ensures the B-cell specificity of its growth-transforming function by exploiting BSAP/Pax5 as a lineage-specific activator of the transforming program.